(untitled) (Baghdad Science Journal, 2025)
Epoxy plates have been made in the laboratory by mixing epoxy resin (A) with, hardener (B) in ratio (A: B) = (2:1), so they made (6) plates of different thickness about (0.95-5.8)mm . The optical properties have been studied like (absorption, transmittance, reflectance, energy gap and fluorescent) also the optical constant were found including (absorption coefficient, extinction coefficient and refraction index) for all plates. The results have shown that by increasing the thickness of plates the absorption intensity increase; at plates thickness (0.95-5.8)mm the absorption intensity were ، (0.20,0.69) respectively , and since absorption peak for epoxy occur in ultraviolet region and exactly at wavelength (330 nm) and energy gap (Eg=3.59(eV)) ; so the plates have transmittance about (60-92)% in visible region . The refraction index for Epoprimer epoxy is (n=1.3) and its reflectance is (R=20 %) at wavelength (330 nm) . While the fluorescence spectrums that result form shifting absorption spectrum (stoke shift) for epoxy plates it differ according to the used plate’s thickness. Where the shift increases toward longer wavelengths the (red shift) with the increase in plates thickness as the results show; so at plate thickness of (0.95, 3 ,5.8)mm the fluorescence spectrum shift was (100,131,140)nm respectively .